Nontargeted analysis of the urine nonpolar sulfateome: a pathway to the nonpolar xenobiotic exposome. (25th September 2016) - Yao, Yuanyuan; Wang, Poguang; Shao, Gang; Del Toro, Liza V. Anzalota; Codero, Jose; Giese, Roger W.
Abstract : Rationale: Testing the urine nonpolar sulfateome can enable discovery of xenobiotics that are most likely to be bioactive. This is based on the fact that nonpolar xenobiotics are more likely to enter cells where they tend to undergo metabolism, in part, to sulfates that are then largely excreted into the urine. Methods: The following sequence of steps, with conditions that achieve high reproducibility, was applied to large human urine samples: (1) competitive nonpolar extraction with a porous extraction paddle; (2) weak anion‐exchange extraction with strong organic washing; and (3) ultrahigh‐performance liquid chromatography (UHPLC)/negative ion matrix‐assisted laser desorption ionization tandem time‐of‐flight mass spectrometery (MALDI‐TOF/TOF‐MS) with recording of ions with signal‐to‐noise (S/N) ≥ 20 that yielded M–1–80 (loss of SO3 ) or m/z 97 (HSO4 − ) upon fragmentation. Results: From a collection of urine samples from six pregnant women, the masses of 1129 putative sulfates were measured. Three lists of candidate compounds (preliminary hits) from these masses were formed by searching METLIN, especially via MATLAB, yielding putative xenobiotic contaminants (35 compounds), steroids (122), and flavonoids (1582). Conclusions: A new way to reveal some of the nonpolar xenobiotic exposome has been developed that applies to urine samples. The value of the method is to suggest xenobiotics for subsequent targeted analysis in the population of people under study, in order to relate the environment to health and disease. Copyright © 2016 John Wiley & Sons, Ltd.